2019
DOI: 10.1007/s00216-019-02101-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel analytical methods to study the fate of mycotoxins during thermal food processing

Abstract: Food processing can lead to a reduction of contaminants, such as mycotoxins. However, for food processing operations where thermal energy is employed, it is often not clear whether a reduction of mycotoxins also results in a mitigation of the toxicological impact. This is often due to the reason that the formed degradation products are not characterized and data on their toxicity is scarce. From the perspective of an analytical chemist, the elucidation of the fate of a contaminant in a complex food matrix is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Feed processing methods, specifically thermal treatment is done in case of soybean, but not any other ingredients that are only crushed into smaller particles. The treatment probably influenced the low aflatoxins content in soybean, although the detection method targeted the primary aflatoxins not the degradation products, which may be equally toxic (Stadler et al 2019). Occurrence of aflatoxins in feed ingredients and raw materials even at lower concentrations will result into overall contamination of the compounded feed posing health risk to the animals (Nemati et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Feed processing methods, specifically thermal treatment is done in case of soybean, but not any other ingredients that are only crushed into smaller particles. The treatment probably influenced the low aflatoxins content in soybean, although the detection method targeted the primary aflatoxins not the degradation products, which may be equally toxic (Stadler et al 2019). Occurrence of aflatoxins in feed ingredients and raw materials even at lower concentrations will result into overall contamination of the compounded feed posing health risk to the animals (Nemati et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies increasingly indicated that high resolution mass spectrometry is a powerful tool in a large scale of mycotoxins screening as well as food and feed comprehensive analyses [35,39]. Castaldo et al examined 89 pet food samples, which then were subjected to a targeted analysis of 28 most common mycotoxins, i.e., Fusarium mycotoxins, aflatoxins and ochratoxin A [35].…”
Section: Discussionmentioning
confidence: 99%
“…The 54% AOH reduction was reported for treatment at 110 °C for 20 min, whereas no significant effect was found for AME at the same temperature [ 58 ]. Based on Stadler et al [ 59 ], the parent mycotoxin can be structurally modified during food processing, including isomerization, decarboxylation, rearrangements, and the reaction with other small molecules [ 59 ]. In summary, food processing such as brewing, cooking, baking, frying, canning flaking, nixtamalization, and extrusion, in general, reduced concentrations of some mycotoxins but did not eliminate them completely [ 52 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%